Adsorption and biodegradation of pollutants from livestock wastewater by aged refuse bioreactor - Chinenyenwa, Anijiofor Sandra (2018)
This study investigated the characteristics of landfilled solid wastes, “aged refuse”, for adsorption and biodegradation processes, as an affordable livestock wastewater treatment option. Presently, the UPM dairy farm discharges about 2000-2200 L/day of untreated wastewater into a nearby river, raising serious environmental concerns, especially regarding water pollution. The parameters studied were pH, chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS), total dissolved solids (TDS), turbidity, total nitrogen (TN), ammonia nitrogen (NH3-N), total phosphorous (TP) and total coliform. Three sources of livestock wastewater (Dairy farm, chicken slaughter house and fishpond), were examined, while the aged refuse was collected from Air Hitam sanitary landfill, Selangor, Malaysia. The results revealed aged refuse characteristics such as pH 7.14, moisture content 29.5%, organic content 9.90%, total coliform 7.1 x 106 CFU/100 mL, which are suitable conditions for biodegradation. Hydraulic conductivity 0.31 cm/s, porosity (n) 51%, and bulk density (ρ) 1.23 g/cm3, are suitable conditions for free water flow and air diffusion. The available exchangeable cations (Ca, Mg, K, Na), will promote ion exchange while low metal concentrations of (Pb = 0.858, Cr = 14.0, Cu = 1.10 and Zn = 12.16 mg/kg), will reduce interference. The scanning electron microscopy (SEM), showed available pore spaces, and BET surface area 3.376 m2/g, which are suitable for adsorption, while the Fourier Transform Infra-red (FTIR), revealed functional groups of carbonyl, carboxyl and hydroxyl groups, with strong adsorption capacity. The batch adsorption study indicated the effects of pH, dosage and contact time on removal efficiency, and optimum conditions were; pH 6, dosage 2-4 g/100 mL, adsorbent size ≤ 2 mm, contact time 10-180 minutes, agitation speed 250 rpm and ambient temperature conditions. The maximum removal efficiency were about 94% (COD, BOD), 91% (TSS, TDS), 97% colour and 88% NH3-N. The correlation coefficient R2 (0.9026 to 0.9999) for Langmuir, and (0.9422 to 0.9999) for Freundlich isotherms, fitted well to experimental data. Furthermore, an aged refuse bioreactor (15 cm diameter and 80 cm height), was developed and used for livestock wastewater treatment at a loading rate of 4 L m3/day and flow rate of 0.1 L/min. The reactor was very effective after over 10 hours retention time which resulted in high removal rates > 90% for COD, BOD5, TSS, Turbidity, Colour, TP and total coliform, TDS = 62%, NH3-N = 60% and TN = 46%. The effluent quality for most of the parameters meet the Malaysian effluent discharge standard B, while alternating aerobic and anaerobic systems were recommended in future development for enhanced nitrogen removal. The Malaysian aged refuse has very significant characteristics such as adequate pore structure and surface characteristics, huge bacteria population, high porosity, high moisture and organic content, and has shown efficient adsorption and biodegradation processes in different livestock wastewater treatment. Moreover, it is a simple and affordable wastewater treatment technology, and therefore proposed for UPM dairy farm to experiment on a larger scale, for future development and application.